2004
DOI: 10.1111/j.0013-9580.2004.06304.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of the New Antiepileptic Drugs, II: Treatment of Refractory Epilepsy: Report of the TTA and QSS Subcommittees of the American Academy of Neurology and the American Epilepsy Society

Abstract: Summary:Purpose: To assess the evidence demonstrating efficacy, tolerability, and safety of seven new antiepileptic drugs (AEDs) [gabapentin (GBP), lamotrigine (LTG), topiramate (TPM), tiagabine (TGB), oxcarbazepine (OXC), levetiracetam (LEV), and zonisamide (ZNS)] in the treatment of children and adults with refractory partial and generalized epilepsies.Methods: A 23-member committee, including general neurologists, pediatric neurologists, epileptologists, and doctors in pharmacy, evaluated the available evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(45 citation statements)
references
References 85 publications
5
37
0
3
Order By: Relevance
“…In a decreasing order, CBZ, CLB, LTG, and TPM were the most commonly prescribed AED found in the present study, which reasonably agrees with important international gui delines that highlight the efficacy and effectiveness of all available 13 or only new AED 14 for treating partial onset seizures, the most prevalent seizure type in adults 15 . Carbamazepine and PHT are considered by ILAE to have the highest evidence level for use in treating refractory epilepsy as initial monotherapy.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In a decreasing order, CBZ, CLB, LTG, and TPM were the most commonly prescribed AED found in the present study, which reasonably agrees with important international gui delines that highlight the efficacy and effectiveness of all available 13 or only new AED 14 for treating partial onset seizures, the most prevalent seizure type in adults 15 . Carbamazepine and PHT are considered by ILAE to have the highest evidence level for use in treating refractory epilepsy as initial monotherapy.…”
supporting
confidence: 90%
“…French and colleagues 14 concluded that all new AED are adequate for use as adjunctive therapy in adults with refractory partial epilepsy. Indeed, there is an international tendency toward increasing prescription of new AED 22 , sometimes even overcoming the number of prescriptions of old AED…”
mentioning
confidence: 99%
“…The responder rates by seizure type were 22 % in SPS, 28% in CPS, 44% in 2 nd GS, and 25% in generalized seizures. Similar to previous reports [8,12], therapeutic effects were seen not only in patients with partial epilepsies and partial seizures, but also in those with generalized epilepsies, generalized seizures, and SMEI. The frequency of adverse events was 54% in our study, which was lower than that of a previous study in Japan (81%) that used an initial dose of 100 mg/day and rapid dose escalation (weekly increment of 100 mg/day) [18,22].…”
Section: Discussionsupporting
confidence: 90%
“…TPM has been proven to be effective as an adjunctive AED for partial epilepsy [5], generalized epilepsy [6], and Lennox-Gastaut syndrome [7]. Its efficacy and safety have been shown by several clinical studies in adult patients, not only in the United States and European countries [8,9], but also in Asian countries including Taiwan [10], Republic of China [11], and Korea [12]. We conducted this investigation to assess the clinical effectiveness and adverse reactions of TPM in Japanese adult patients with refractory epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the remaining 20 -30% of patients will continue to experience intractable seizures or have significant adverse reactions to AEDs. 1,126 In patients with refractory CPS, the overall risk of death (whether due to accident, suicide, or SUDEP) is very high, compared with age-matched, healthy people. 127 Heart rate abnormalities have been found to accompany CPS in drug-resistant children and adolescents, which may contribute to the occurrence of SUDEP.…”
Section: Consequences Of Uncontrolled Seizuresmentioning
confidence: 99%